Research on the Phase Transformation of a Newly Developed Carbonitride-Strengthened Martensitic Heat Resistant Steel - Zhang, Wenfeng; Pan, Ping; Zhou, Jun; Xiong, Wei; Liu, Yunqiang; Liu, Xiaogang; Yan, Wei (Frontiers in Materials, 2022)
The phase transformation behavior of nitrides strengthened martensitic (NSM) heat resistant steel, showing excellent creep behavior under 500oC, was studied in this article. The results showed that during the heating procedure, the formation of austenite was composed successively by intermetallic compound formation in martensite, crystal structure shift from body-centered cubic (BCC) to face-centered cubic (FCC), martensite/ferrite grain boundary migration, austenite nucleation and growing. The crystal structure switch from BCC to FCC was sensitive to temperature, while the switch from FCC to BCC was only in company with phase transformations. During the continuous cooling procedure, the non-compound bainite would form if the cooling rate was beneath the critical cooling rate. 0.5oC/s cooling rate was defined to be the critical cooling rate for single martensite in NSM steel, according to its inconsistent results of microstructure and continuous cooling transformation (CCT) expansion curve under this condition. Two phase transformation zone were detected in NSM steel: one was nose-shaped bainite zone and the other was stripe-shaped martensite zone.